Intraoperative Dexmedetomidine Versus Midazolam in Patients Undergoing Peripheral Surgery With Mild Traumatic Brain Injuries: A Retrospective Cohort Analysis - Jing Peng; Fujuan He; Chenguang Qin; Yuanyuan Que; Rui Fan; Bin Qin (SAGE Publishing, 2020)
Background: The intra- and postoperative effects of dexmedetomidine are not completely consistent and midazolam/fentanyl is most widely used in peripheral surgeries. The objectives of the study were to evaluate the sedative, analgesic, hemodynamic, anti-inflammatory, and antioxidant effects of dexmedetomidine against midazolam in patients undergoing peripheral surgeries with mild traumatic brain injuries. Methods: Medical records of patients who underwent peripheral surgeries with mild traumatic brain injury were included in the analysis. Patients received intraoperative midazolam (MDZ cohort, n = 225) or dexmedetomidine (DEX cohort, n = 231). Pre-, intra-, and postoperative characteristics of patients were collected and analyzed. Results: After administration of anesthesia, up to 40 minutes, patients of the MDZ group had lower modified observer's assessment of alertness/sedation score than those of the DEX group ( P = .041), but after 40 minutes, patients of the MDZ group had a higher score than those of the DEX group throughout surgeries ( P = 0.048). The DEX group has less requirements of postoperative morphine/equivalent doses than the MDZ group (4 ± 1 vs 5 ± 1, P < .0001, q = 18.451). Conclusions: Intraoperative DEX offers better sedation, postoperative analgesia, and clinical recovery for peripheral surgeries and suppresses inflammatory response. Level of Evidence: III.